TRANSCARPATHIAN HUNGARIANS AND THEIR LINGUISTIC ADVENTURES IN HUNGARY - Csernicskó, István (Linguistic Bulletin (Movoznavchyi Visnyk), 2024)
Introduction. On February 24, 2022, the Russian Federation, in violation of international law, launched a full-scale war against Ukraine. As a result of the war, millions of Ukrainian citizens were forced to flee abroad. In the early days of the conflict, several thousand members of the Hungarian national minority living in the Transcarpathia region of Ukraine also fled abroad, primarily to Hungary. These Ukrainian citizens are ethnically Hungarian and consider Hungarian their native language. However, upon arriving in Hungary, they suddenly found themselves in a monolingual environment, whereas at home, they were accustomed to a multilingual setting. In their daily lives, it was common for them to handle official matters in the state language (Ukrainian), receive utility bills in Ukrainian, and live bilingually – using both Hungarian and Ukrainian. After arriving in Hungary, the change in the linguistic environment further complicated their integration. The purpose. The purpose of the article is to show, on the basis of research data, how Transcarpathian Hungarians who arrived in Hungary after the invasion of Ukraine perceive the linguistic environment of the host country, what differences and similarities they perceive between their language variants and the Hungarian linguistic environment, and how this is reflected in the linguistic behaviour of the war refugees. Results. In the spring of 2022, 120 Hungarians from Transcarpathia who arrived in Hungary after the start of the full-scale invasion completed an online survey. This survey examined the linguistic challenges faced by Hungarians who relocated from Ukraine to Hungary. The survey was supplemented by interviews: in the summer of 2022, 18 interviews were conducted, focusing on the language adaptation of Transcarpathian Hungarians in Hungary. The research revealed that Transcarpathian Hungarians who settled in new dialectal environments similar to their native ones encountered significantly fewer linguistic challenges than those who settled in more distant regions of Hungary. Hungarians who arrived in Hungary strive to adapt their language practices to the linguistic norms of their new surroundings. At the same time, the linguistic characteristics they brought from home connect them to their homeland and form part of their regional identity. Thus, the Hungarian language, on the one hand, unites Hungarians living in any part of the world, while on the other hand, its diversity allows for the expression of unique identity. Originality. For the first time, an empirical study was conducted to find out how Transcarpathian Hungarians who arrived in Hungary after 24 February 2022 perceive the linguistic practice of the Hungarian environment in which they have found themselves, what differences and similarities they perceive between their own language variants and language use in Hungary, and what reflections this provokes among war refugees. Conclusions. The results of the online survey and interviews are summarised according to the following criteria: attitudes towards the Hungarian dialects of Transcarpathia; differences between Hungarian in Hungary and Hungarian in Transcarpathia; communication failures and stigmatisation; problems with the use of official vocabulary; use of Slavic loanwords; language and identity; and the role of dialectal background. In the long term, we hope to investigate how Hungarians in Hungary perceive Transcarpathian Hungarians and the linguistic variants they use.